Comparative Analysis of River Capacity with Maximum Discharge in Ngotok Ring Canal - Widodo, Yudo Wahyu; Asmaranto, Runi; Dermawan , Very (International Journal Labs, 2025)
Flooding in the Ngotok Ring Canal is a recurring problem, primarily caused by intense rainfall, elevated water levels of the Brantas River, and the limited capacity of the canal's flow. This issue is especially evident at the confluence points of the Ngotok Ring Canal with its tributaries, where backwater effects or puddling occur. The objective of this study is to analyze the flood dynamics in the Ngotok Ring Canal, specifically evaluating the rise in floodwater levels and necessary mitigation measures. The analysis was conducted using the HEC-RAS program to model existing river conditions and assess flood risks. The study identifies that the embankment height at the upstream section of the Ngotok River is insufficient to contain the flood discharge, leading to overflow into surrounding agricultural fields. The flood design for the Ngotok River, based on a 25-year return period, was determined to be 866.29 m³/sec. The proposed solution involves an economical embankment design with a 1:1.25 slope, ensuring that the floodwater level remains below the average land elevation. This design approach addresses both floodwater containment and cost-efficiency in construction, providing a sustainable solution to reduce flooding risks in the area.